2020
DOI: 10.1016/j.ajem.2019.03.041
|View full text |Cite
|
Sign up to set email alerts
|

N95 filtering facepiece respirators do not reliably afford respiratory protection during chest compression: A simulation study

Abstract: a b s t r a c tBackground: N95 filtering facepiece respirators (N95 respirators) may not provide adequate protection against respiratory infections during chest compression due to inappropriate fitting. Methods: This was a single-center simulation study performed from December 1, 2016, to December 31, 2016. Each participant underwent quantitative fit test (QNFT) of N95 respirators according to the Occupational Safety and Health Administration protocol. Adequacy of respirator fit was represented by the fit fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
1
42
0
4
Order By: Relevance
“…2 Some studies have also suggested that N95 respirators fail to protect HCWs during strenuous activities such as performing chest compressions. 8,9 In line with studies by Lee et al 10 and McMahon et al, 11 women had higher fit failure rates compared with men. We observed a similar pattern with fit testing of standard respirators.…”
Section: Discussionsupporting
confidence: 73%
“…2 Some studies have also suggested that N95 respirators fail to protect HCWs during strenuous activities such as performing chest compressions. 8,9 In line with studies by Lee et al 10 and McMahon et al, 11 women had higher fit failure rates compared with men. We observed a similar pattern with fit testing of standard respirators.…”
Section: Discussionsupporting
confidence: 73%
“…Maranhao et al ( 32 ) reported higher probability of fit testing failure with commercial disposable N95 respirators when re-used and sterilized after 4 days of continuous use. Further, activities in close approximation to patients, such as cardiopulmonary resuscitation, reduce efficacy of N95 in those that would otherwise pass fit testing ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to facial habitus, duration of procedure, and need for uncommon positioning and movement of the head on the neck during procedures for visualization. 23,24 Additionally, the tight seal needed for N95s with their nonadjustable bands can cause significant facial trauma and respiratory compromise to health care workers over repeated use or after procedures of long duration. 25,26 For standard airborne precautions, N95 masks are appropriate for respiratory protection.…”
Section: Identification Of High-risk Procedures and Aerosol-generatinmentioning
confidence: 99%